STUDENTS PERCEPTION ON THE USE OF VIDEO TO ASSESS PERFORMANCES IN PUBLIC SPEAKING CLASS - Pratiwi, Septi Widhiayu; Triprihatmini, Veronica (LLT Journal: A Journal on Language and Language Teaching, 2018)
This paper attempts to recognize the use of video as teaching and learning aid related to students perception. As survey research, it focuses on finding the students perception on the use of video to assess students performances in Public Speaking class. In addition to that, this paper presents the discussion about the implication of the students perception on the use of video to assess their public speaking performances. It is found that the students have good or positive perception and the use of video is beneficial to identify their strengths and weaknesses in public speaking performance. Therefore, the students are encouraged to perform better in public speaking. It implies that video is an appropriate teaching and learning aid for Public Speaking students and the lecturers themselves have contributed well in assisting the students in the activities using video in Public Speaking class.